Tafsir, ta’wil, dan terjemahan al-qur’an: Analisis metodologis, keterkaitan, dan implikasi kontemporer - Erika, Febby; Anwar, Abu; Azmira, Nur; Pangestu, Endy Dharma (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
This study examines the methodological relationships and distinctions among Qur’anic exegesis (tafsir), interpretation (ta’wil), and translation. Tafsir emphasizes explaining the apparent meanings of verses through textual, historical, and linguistic approaches. Ta’wil explores deeper or symbolic meanings, while translation conveys the message into another language to ensure wider accessibility. Using a qualitative and literature-based approach, this research analyzes classical and contemporary works to formulate operational boundaries and criteria of validity. The findings highlight the importance of conceptual clarity, methodological accuracy, and linguistic precision in producing a more comprehensive understanding of the Qur’an.